2014
DOI: 10.1158/0008-5472.can-14-0799
|View full text |Cite
|
Sign up to set email alerts
|

SAR405838: An Optimized Inhibitor of MDM2–p53 Interaction That Induces Complete and Durable Tumor Regression

Abstract: Blocking the MDM2-p53 protein-protein interaction has long been considered to offer a broad cancer therapeutic strategy, despite the potential risks of selecting tumors harboring p53 mutations that escape MDM2 control. In this study, we report a novel small molecule inhibitor of the MDM2-p53 interaction, SAR405838 (MI-77301) that has been advanced into Phase I clinical trials. SAR405838 binds to MDM2 with Ki = 0.88 nM and has high specificity over other proteins. A co-crystal structure of the SAR405838:MDM2 co… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
278
0
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 281 publications
(284 citation statements)
references
References 40 publications
4
278
0
2
Order By: Relevance
“…Their frequent presence in the root of cancer lineages implies that they play key formative roles in the origin of cancer and that they deserve redoubled attention for their roles in tumorigenesis. The potential to therapeutically target these longstanding drivers of cancer continues to evolve, including targeting TP53 via the TP53/MDM2 interaction (20), targeting KRAS via KRAS G12C (21), targeting posttranslational modifications of KRAS (22), or targeting upstream or downstream effectors (23).…”
Section: Ancestral State Reconstruction Revealed the Temporal Occurrencementioning
confidence: 99%
“…Their frequent presence in the root of cancer lineages implies that they play key formative roles in the origin of cancer and that they deserve redoubled attention for their roles in tumorigenesis. The potential to therapeutically target these longstanding drivers of cancer continues to evolve, including targeting TP53 via the TP53/MDM2 interaction (20), targeting KRAS via KRAS G12C (21), targeting posttranslational modifications of KRAS (22), or targeting upstream or downstream effectors (23).…”
Section: Ancestral State Reconstruction Revealed the Temporal Occurrencementioning
confidence: 99%
“…Screening of R/S isomers of ligands L1-L11 provided (S)-L11 as most potent inhibitor of p53-MDM2 interaction. (S)-L11 showed the MDM2 binding pattern similar to that of reference, nutlin-3a and SAR405838 [17,18]. It successfully mimics three crucial residues (Phe19, trp23, and Leu26) of p53 in binding cavity on MDM2 (Fig.…”
Section: Docking Study Of Nutlin-3a Sar405838 and L0-l11 In Mdm2mentioning
confidence: 64%
“…Spiro(oxindole-3,3 0 -pyrrolidine) emerged as the most potent class of MDM2 inhibitors with high binding affinities to MDM2, cellular potencies, and significantly optimized pharmacokinetic properties. They effectively induced complete tumor regression in the SJSA-1 osteosarcoma xenograft model in mice and have high specificity over other proteins [77]. Various synthetic spiro-oxindoles were identified through structure-based drug design [78].…”
Section: Spiro-oxindoles As Novel Class Of Selective and Potent Mdm2 mentioning
confidence: 99%
“…The newly developed enantiomer MI-773-01 displayed 10 times higher binding affinity against MDM2 than MI-773 did. The antitumor activity of MI-773-01 (SAR405838) was more pronounced in a set of wild-type p53 xenograft models including osteosarcoma, human prostate, melanoma, colorectal tumor, and acute lymphoblastic leukemia [77]. Compound MI-773-01 (SAR405838) was advanced into phase I clinical trials by Sanofi in 2012 and results showed that the treatment of SJSA-1 osteosarcoma cell lines with SAR405838 in vitro leads to dose-dependent cell growth inhibition, cell cycle arrest, and robust apoptosis [86].…”
Section: 1 Spiro-pyrrolidinyl-based Inhibitorsmentioning
confidence: 99%